The Doctrine of Khiyar al-Ayb in Protecting the Customer’s Rights - Faizah Syihab (Akademika: Jurnal Keagamaan dan Pendidikan, 2016)
Khiyar is a theory of option in Islamic Law of Mu`amalat which made upon protecting the right of related parties in transaction. While, Khiyar Al-`Ayb is one of the components which highlights the caption on option due to defects which give the party at the deficient place or buyers an option to not obliged to the contract as might cause an offend or oppress to them. It is deemed as an important provision to enclose together in the contract term to exercise the Khiyar Al-‘Ayb as the natural right of the buying party. This paper attempts to address challenges endure and its prospects through this doctrine of option in realizing it in today immense transaction. Furthermore, there are some example cases in the real practice which before and after the practicing of Khiyar Al-`Ayb in the stipulated contract terms and condition.